2016
DOI: 10.3390/s16091431
|View full text |Cite
|
Sign up to set email alerts
|

Web of Objects Based Ambient Assisted Living Framework for Emergency Psychiatric State Prediction

Abstract: Ambient assisted living can facilitate optimum health and wellness by aiding physical, mental and social well-being. In this paper, patients’ psychiatric symptoms are collected through lightweight biosensors and web-based psychiatric screening scales in a smart home environment and then analyzed through machine learning algorithms to provide ambient intelligence in a psychiatric emergency. The psychiatric states are modeled through a Hidden Markov Model (HMM), and the model parameters are estimated using a Vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In these papers, the authors make use of a variety of different types of sensors. In [17], Brennan et al In the identified papers, the reasons for using the Discriminant Analysis method with sensor devices in smart buildings were equally distributed between human activity recognition/classification [16,17,62] and the detection of human behavior in the context of assisted living [33,61,66].…”
Section: Classificationmentioning
confidence: 99%
See 3 more Smart Citations
“…In these papers, the authors make use of a variety of different types of sensors. In [17], Brennan et al In the identified papers, the reasons for using the Discriminant Analysis method with sensor devices in smart buildings were equally distributed between human activity recognition/classification [16,17,62] and the detection of human behavior in the context of assisted living [33,61,66].…”
Section: Classificationmentioning
confidence: 99%
“…The authors of [66] implemented the Discriminant Analysis technique. In [33], the authors implemented a Hidden Markov Model (HMM), Viterbi path counting, and a scalable Stochastic Variational Inference (SVI)-based training algorithm, along with Generalized Discriminant Analysis. In [62], the authors made use of various methods of feature extraction (Principal Component Analysis (PCA), Independent Component Analysis (ICA), and Linear Discriminant Analysis (LDA)) and the new features selected by each method were subsequently used as the inputs for a Weighted Support Vector Machines (WSVM) classifier.…”
Section: Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel approach identified for detection of conditions is the use of unstructured text, including detection of suicide ideation from counselling transcripts [10], detection of schizophrenia from written texts [11], and analysis of social media data to detect depressive symptoms [12]. ML has also been applied to wearable sensor data to assess general wellbeing [13], and to ambient, in-home sensors to detect psychiatric emergencies [14]. Finally, speech data has been used with ML to detect underlying mental states indicative of schizophrenia and depression [15], to assess the effects of drugs on mental state [16], and to classify at-risk patients of Alzheimer's disease based on speech patterns [17].…”
Section: Detection and Diagnosismentioning
confidence: 99%